AKIBAT HUKUM NOTARIS YANG MEMBUAT AKTA MEMPUNYAI KEDUDUKAN DALAM PERSEROAN TERBATAS - Harla Ratda (El-Iqthisadi, 2019)
AbstractThe legal power of a limited liability company (PT) if it involves a Notary as a governing body and a shareholder in a limited liability company (PT) then the notary deed only has the force of law as a deed under the hand because the Notary has violated the code of ethics listed in the rules of office Notary as well as violate Law No. 30 of 2004 regarding the position of Notary and Article 20 PJN. The legal consequence of a Notary having a position in a limited liability company (PT) is the birth of a deed of establishment of a limited liability company (PT) null and void of execution powers if the Notary that made the deed had a limited liability company (PT) may be involved or have interest in a limited liability company (PT).Keywords: Notary, Limited Company SharesAbstrakKekuatan hukum suatu akta pendirian perseroan terbatas (PT) jika melibatkan Notaris sebagai pengurus serta pemegang saham dalam sebuah perseroan terbatas (PT) maka akta Notaris tersebut hanya mempunyai kekuatan hukum sebagai akta dibawah tangan, karena Notaris tersebut telah melanggar kode etik yang tercantum dalam peraturan jabatan Notaris serta melanggar Undang-undang No. 30 Tahun 2004 tentang jabatan Notaris serta pada Pasal 20 PJN. Akibat hukum yang timbul bilamana seorang Notaris mempunyai kedudukan dalam sebuah perseroan terbatas (PT) yakni kelahiran sebuah akta pendirian suatu perseroan terbatas (PT) batal demi hukum serta tidak mempunyai kekuatan eksekutorial jika Notaris yang membuat akta itu mempunyai kedudukan dalam perseroan terbatas (PT) tidak boleh terlibat atau mempunyai kepentingan dalam perseroan terbatas (PT).Kata Kunci : Notaris, Saham Perseroan Terbatas